Water security - Jagerskog, Anders; Swain, Ashok; Ojendal, Joakim (Sage library of international security, 2014)
The four volumes of this collection broadly outline the debate as it has developed, both from a policy as well as an academic perspective, bringing conceptual clarity as well as providing an account of how the water security discourse has emerged and developed.